Landscape of genes in hospital wastewater breaking through the defense line of last-resort antibiotics. (1st February 2022) - Zhu, Lin; Shuai, Xin-Yi; Lin, Ze-Jun; Sun, Yu-Jie; Zhou, Zhen-Chao; Meng, Ling-Xuan; Zhu, Yong-Guan; Chen, Hong
Highlights: Chlorine disinfection could effectively reduce the absolute abundance of most last-resort ARGs. Conjugation efficiencies of plasmids carrying last-resort ARGs were 2.41 × 10−6 ∼ 4.00 × 10−5. 7 plasmids with diversified replication incompatibilities were dissected. Co-occurrence of two unique plasmids was detected in a single E. coli. Alignment of last-resort ARGs and flanking sequences revealed the varied genetic environments. Abstract: Hospital wastewater contains abundant antibiotics, antibiotic resistance genes (ARGs), and pathogens. Last-resort antibiotic resistance genes (LARGs) include the New Delhi metallo-β-lactamase gene bla NDM, mobile colistin resistance gene mcr and tigecycline resistance gene tet (X) which confers resistance to carbapenems, colistin and tigecycline. The presence and significance of LARGs in hospital wastewater treatment systems (HWTS) have not yet been systematically explored. Here, LARG variants were shown to be prevalent both influents and effluents of HWTS. A total of 989 Enterobacteriaceae isolates that confer resistance to last-resort antibiotics were collected from effluents and multiple genetic contexts of LARGs were analyzed. LARGs-carrying plasmids were confirmed to show high multidrug phenotypes and transferability. We also discovered the co-occurrence of plasmids harboring bla NDM-1 and mcr-1 in single Escherichia coli, as well as E. coli HM016 containing two unique mcr-1 -carrying plasmids. This result might accelerate co-dissemination of LARGs under environmental selection pressure. Different core genetic arrangements in these strains suggest several evolutionary pathways in HWTS. The resistance functions of LARGs were confirmed in vitro and in vivo by mass spectrometry. This study provides novel insights into the diversity, genetic context and function of critical ARGs in HWTS. The results raise the concern that LARGs may further spread into the environment, thus, more stringent discharge standards and regulations for hospital wastewater are urgently needed. Graphica abstract: Image, graphical abstract